Conceptual and theoretical understanding of the phenomenon of tolerance: historical and philosophical digression - Kurbacheva, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to analysis of the phenomenon of tolerance, which is one of the most topical issues in modern socio-humanitarian thought. Therefore, this article aims to analyze the essential grounds of the phenomenon of tolerance and to carry out the historical and philosophical background of the concept in the Western European and Russian philosophy. Identify the aspects of tolerance, moral-psychological and moral-political aspects of tolerance. Is denoted by the variable, dynamic and polysemantic nature of tolerance as a concept and the existence of socio-cultural determination in the interpretation of tolerance as a phenomenon. The emphasis understanding of tolerance as a space of free and informed choice in the dialogue.